Design of external pressure test rigs for marine riser - Seow, Shao wei. (2013)
Production risers play an important role in transporting oil and gas from the oils well to the surface. With the necessity to explore into deep sea, composite material is seen as the next generation of materials for manufacturing the production risers. Being a relatively new material to the marine industry, testing for composite risers has not been widely developed. This report cross referenced from existing metal riser standards to design a test rig that is suitable to perform collapse failure testing on scaled down composite riser specimens. The designed test rig aims to identify the first sign of collapse failure on the scaled down composite riser specimen by hydrostatic pressure.